Memphis Tennessee Garrison : the remarkable story of a Black Appalachian woman - Garrison, Memphis Tennessee, 1890-1988 (Ohio University Press series in ethnicity and gender in Appalachia., 2001)
"As a black Appalachian woman, Memphis Tennessee Garrison belonged to a group triply ignored by historians." "The daughter of former slaves, she moved with her family to McDowell County, West Virginia, at an early age. The coalfields of McDowell County were among the richest in the nation, and Garrison grew up surrounded by black workers who were the backbone of West Virginia's early mining work force - those who laid the railroad tracks, manned the coke ovens, and dug the coal. These workers and their families created communities that became the centers of black political activity - both in the struggle for the union and in the struggle for local political control. Memphis Tennessee Garrison, as a political organizer, and ultimately as vice president of the National Board of the NAACP at the height of the civil rights movement (1963-66), was at the heart of these efforts." "Based on transcripts of interviews recorded in 1969, Garrison's oral history is a rich, rare, and compelling story. It portrays African American life in West Virginia in an era when Garrison and other courageous community members overcame great obstacles to improve their working conditions, to send their children to school and then to college, and otherwise to enlarge and enrich their lives."--Jacket